Nilai Spiritual Manunggaling Kawula Gusti dalam Motif Batik Kawung - Widayanti, Firda Mutia; Handayani, Tri (Faculty of Humanities, Diponegoro University, 2024)
This study aims to explore the values of “Manunggaling Kawula Gusti” contained in the kawung batik motif, which contains deep philosophical meaning in Javanese culture. “Manunggaling Kawula Gusti” is a teaching that emphasizes the union between man (kawula) and God (Gusti), describing an individual's spiritual journey towards awareness of the divine presence in every aspect of life. This teaching is often associated with Sheikh Siti Jenar, a controversial figure in Javanese history, who taught that God is a being that transcends everything, encompassing both the material and mental realms in their entirety. Sheikh Siti Jenar, who introduced the view that God is a being that encompasses the entire universe, both matter and soul, and transcends the understanding of human senses. On the other hand, the kawung batik motif is one of the classic batik motifs that has a repeating elliptical geometric pattern. This motif is not only appreciated for its beauty but also for its deep symbolic meaning. Kawung batik symbolizes the harmony between microcosm (humans) and macrocosm (the universe) and reminds humans of the importance of maintaining balance and harmony in life. This motif also reflects the teaching of “Sedulur Papat Limo Pancer”, which teaches about the four main directions that symbolize the elements of life that must be balanced with conscience as the center. This research uses the literature study method by analyzing various journal articles and relevant books. The results show that there is a strong philosophical connection between the concept of “Manunggaling Kawula Gusti” and the Batik Kawung motif. This motif is not only an artistic expression but also a visual reminder for Javanese people of the importance of maintaining a harmonious relationship with God, fellow humans, and nature. Batik Kawung, with its spiritual meaning, represents the teachings of “Manunggaling Kawula Gusti”.This study aims to explore the values of “Manunggaling Kawula Gusti” contained in the kawung batik motif, which contains deep philosophical meaning in Javanese culture. “Manunggaling Kawula Gusti” is a teaching that emphasizes the union between man (kawula) and God (Gusti), describing an individual's spiritual journey towards awareness of the divine presence in every aspect of life. This teaching is often associated with Sheikh Siti Jenar, a controversial figure in Javanese history, who taught that God is a being that transcends everything, encompassing both the material and mental realms in their entirety. Sheikh Siti Jenar, who introduced the view that God is a being that encompasses the entire universe, both matter and soul, and transcends the understanding of human senses. On the other hand, the kawung batik motif is one of the classic batik motifs that has a repeating elliptical geometric pattern. This motif is not only appreciated for its beauty but also for its deep symbolic meaning. Kawung batik symbolizes the harmony between microcosm (humans) and macrocosm (the universe), and reminds humans of the importance of maintaining balance and harmony in life. This motif also reflects the teaching of “Sedulur Papat Limo Pancer”, which teaches about the four main directions that symbolize the elements of life that must be balanced with conscience as the center. This research uses the literature study method by analyzing various journal articles and relevant books. The results show that there is a strong philosophical connection between the concept of “Manunggaling Kawula Gusti” and the Batik Kawung motif. This motif is not only an artistic expression but also a visual reminder for Javanese people of the importance of maintaining a harmonious relationship with God, fellow humans, and nature. Batik Kawung, with its spiritual meaning, represents the teachings of “Manunggaling Kawula Gusti”.